Why rapid, adaptive evolution matters for community dynamics - Koch, Hanna; Frickel, Jens; Valiadi, Martha; Becks, Lutz (Frontiers in Ecology and Evolution, 2014)
Evolution on contemporary timescales has recently been recognized as an important driver for ecological change. It is now well established that evolutionary change can affect the interactions between species within a few generations and that ecological interactions may influence the outcome of evolution in return. This tight link between ecology and evolution is of fundamental importance as it can determine the stability of populations and communities, as well as the generation and maintenance of diversity within and among populations. Although these eco-evolutionary dynamics and feedbacks have now been demonstrated many times, we are still far away from understanding how often they occur in nature. We summarize recent findings on eco-evolutionary dynamics, with a focus on consumer-resource interactions, from theory and empirical research. We identify gaps in our knowledge and suggest future research directions to provide a mechanistic understanding and predictive capability for community and ecosystem responses to environmental change.